Alterations of Cerebral Blood Flow and its Connectivity Patterns Measured with Arterial Spin Labeling in Mild Cognitive Impairment - Qiu, Mingjuan; Zhou, Di; Zhu, Haiyan; Shao, Yongjia; Li, Yan; Wang, Yibin; Zong, Genlin; Xi, Qian (Current Alzheimer research, 2023)
Cerebral blood flow (CBF) is an important index for measuring brain function. Studies have shown that regional CBF changes inconsistently in mild cognitive impairment (MCI). Arterial spin labeling (ASL) is widely used in the study of CBF in patients with MCI. However, alterations in CBF connectivity in these patients remain poorly understood. In this study, 3D pseudo-continuous arterial spin labeling (3D-pCASL) technology was used to investigate the changes in regional CBF and CBF connectivity between 32 MCI patients and 32 healthy controls. The normalized CBF was used to reduce inter-subject variations. Both group comparisons in the CBF and correlations between CBF alterations and cognitive scores were assessed. CBF connectivity of brain regions with regional CBF differences was also compared between groups. We found that compared with that in controls, the CBF was significantly reduced in the left superior parietal gyrus in MCI patients, whereas it was increased in the left precentral gyrus, right superior temporal gyrus, right putamen, and left supplementary motor area. In patients with MCI, significant correlations were identified between CBF and neuropsychological scales. Importantly, MCI patients exhibited CBF disconnections between the left supplementary motor area and the left superior parietal gyrus. This study found that there are not only changes in regional CBF but also in CBF connectivity patterns in MCI patients compared with controls. These observations may provide a novel explanation for the neural mechanism underlying the pathophysiology in patients with Alzheimer's disease and MCI.